With complex Langevin towards the QCD phase diagram - Attanasio, Felipe; Jäger, Benjamin; Ziegler, Felix P. G. (Arxiv, 2021)
We use complex Langevin simulations to explore the QCD phase diagram over a large range of chemical potentials and temperatures. For our simulations we use two flavours of dynamical Wilson fermions with a pion mass of approximately 480 MeV with a spatial volume of 243. Here we report on consistency checks at zero chemical potentials and present our results for the fermion density and the Polyakov loop. We find that at the lowest temperature the fermion density remains zero until 𝑚𝑁 3, in line with the expectations from the Silver Blaze phenomenon.
Gesehen am 09.01.2024